2012
DOI: 10.1021/ol301400e
|View full text |Cite
|
Sign up to set email alerts
|

Calophyline A, a New Rearranged Monoterpenoid Indole Alkaloid from Winchia calophylla

Abstract: Calophyline A (1), a novel unprecedented rearranged monoterpenoid indole alkaloid, along with a new natural product N-methyl aspidodasycarpine (2) and six known analogues, was isolated from the trunk barks of Winchia calophylla. The structure of compound 1 was elucidated on the basis of spectroscopic data and then confirmed by a single-crystal X-ray crystallographic analysis. A hypothetical biogenetic pathway for compound 1 was proposed. All isolated compounds were evaluated for their in vitro cytotoxicity aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…[7] In the past decades, considerable efforts have been directed toward synthetic studies of these alkaloids. [8][9][10][11] These studies have resulted in three total syntheses of vincorine (5), [9] two total syntheses of scholarisine A (6), [10] and a total synthesis of aspidophylline A in 2011 by the Garg research group. [11] In pursuit of a general strategy for assembling akuammiline alkaloids, we recently completed the enantioselective total synthesis of vincorine [9b] by using an intramolecular oxidative coupling [8i, k 12, 13] between indole and malonate moieties as the key step.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7] In the past decades, considerable efforts have been directed toward synthetic studies of these alkaloids. [8][9][10][11] These studies have resulted in three total syntheses of vincorine (5), [9] two total syntheses of scholarisine A (6), [10] and a total synthesis of aspidophylline A in 2011 by the Garg research group. [11] In pursuit of a general strategy for assembling akuammiline alkaloids, we recently completed the enantioselective total synthesis of vincorine [9b] by using an intramolecular oxidative coupling [8i, k 12, 13] between indole and malonate moieties as the key step.…”
mentioning
confidence: 99%
“…Since akuammiline (1, Scheme 1) was characterized in 1932, [1] more than 100 akuammiline monoterpenoid indole alkaloids have been discovered from different medicinal plants. [2][3][4][5] Preliminary studies have indicated that these natural products possess a wide range of biological activity, such as the reversal of drug resistance in drug-resistant KB cells by aspidophylline A (2), [3] the in vivo antiinflammatory and analgesic activity exhibited by pseudoakuammigine (3), [6] and the mixed type of competitive and noncompetitive antagonism displayed by corymine (4) at the glycine receptor. [7] In the past decades, considerable efforts have been directed toward synthetic studies of these alkaloids.…”
mentioning
confidence: 99%
“…Mass spectrometry (MS), especially tandem mass spectrometry (MS/MS), is an important physicochemical method for the identification of alkaloids such as vinca alkaloids [8], plumeran indole alkaloids [9], epipolythiodioxopiperazines [10, 11], communesins [12], and uleine alkaloids [13]. In our laboratory, three monoterpenoid indole alkaloids with unique skeletons, that is echitaminic acid, N b -demethylechitamine, and N-methyl aspidodasycarpine, were isolated from the trunk barks of Winchia calophylla [14][15][16][17]. To our knowledge, these indole alkaloids have not been studied in detail by electrospray ionization (ESI)-MS/MS.…”
mentioning
confidence: 99%
“…1), were isolated from the trunk bark of Winchia calophylla. [14][15][16] To our knowledge, uleine alkaloids have not been studied in detail by electrospray ionization (ESI)-MS/MS. The aim of the study was to obtain sufficient information on the structural elucidation of this class of compounds, such as their degradation products, metabolites, and biosynthetic intermediates.…”
mentioning
confidence: 99%
“…The uleine alkaloids were isolated from the trunk bark of Winchia calophylla. [16] MS experiments were performed on a Bruker micrOTOF-Q mass spectrometer (Bremen, Germany). The mass resolution was 10 000 FWHM (full width at half maximum) at 922 u. Argon was used as the collision gas and high-purity nitrogen as the nebulizer and drying gas at flow rates of 0.3 and 4.0 L/min, respectively.…”
mentioning
confidence: 99%